Improving Surface Quality of Additive Manufactured Metal Parts by Magnetron Sputtering Thin Film Coating - Sagbas, Binnur; Yuce, Huseyin; Durakbasa, Numan M. (SPRINGER-VERLAG SINGAPORE PTE LTD, 2022)
Laser powder bed fusion is a novel production technology that generates 3D geometries from CAD data of a functional part. It is a kind of additive manufacturing (AM) process that builds up the geometries layer-by-layer. Because of its layer based nature surface quality of manufactured parts is not its required level. Post processing operations such as sand blasting, shot peening, polishing, heat treatment and coating, are effective choice to increase surface quality of the AM parts. In this study, it is aimed to define ability of titanium thin film coating on the metal based additive manufactured surfaces as a transition layer, by DC magnetron sputtering. Preliminary results of an ongoing study which focused on generating multilayered hard coatings on to the AMmanufactured AlSi10Mg substrates were reported. Surface roughness and friction coefficients of the samples were decreased while hardness and wettability were slightly increased by thin film coating of the substrates.
Keywords: Additive manufacturing; Post processing; AlSi10Mg; Surface quality; Coating; POWDER BED FUSION; HEAT-TREATMENT; MECHANICAL-PROPERTIES; LASER; MICROSTRUCTURE; LAYER; Computer Science; Engineering